The importance of Usage the Artificial Intelligence Applications in Industrial Organization - J. Wahab, Ryad; N. Izzat, Hussein (Opción, 2019)
The rapid technology advancing in world Impose on the plants the strive to adopting or relying on the modern technologies in order to Keep up with the developments , and eventually to achievement beneficial & gain advantages , and improve the position & reputation among the competitive industries . Among the prominent challenging that encountered industry plant is emerg- ing the intelligent devices , machines , & equipments that gained the industry more from excellent advantages & characteristics , this is what called “ Arti- ficial Intelligence “ . this paper attempts to introduction concept of AI , main its components , & areas its applications . measure the degree of availability & ready the field under research to accommodation or encompass like this technique .